Effect of soilless substrate components on the growth and quality of Brassica oleracea L. var alboglabra - Raveenthran, Thilagawathy (2015)
A study was conducted to examine the effect of soilless substrate components on the growth and quality of Brassica oleraceae L. var alboglabra (Kai-lan). A pot experiment was carried out under rain shelter at Ladang 2, Universiti Putra Malaysia, Serdang. The main objective of this study was to evaluate the effect of compost and peatgro and their combination with coconut coir dust and rice husk on the growth, nutrient elements and antioxidant of Kailan. The experiment was arranged in Randomized Complete Block Design (RCBD) with six replications. The treatments (v/v) were 75% compost + 25% coconut coir dust, 75% compost + 25% rice husk, 75% peatgro + 25% coconut coir dust, 75% peatgro + 25% rice husk, 100% compost and 100% peatgro. Substrates were analyzed for water holding capacity, pH and nutrient concentration. Plant height, number of leaves, leaf area, relative leaf chlorophyll content, nutrient concentration and antioxidant compounds were measured. The growth and quality of Brassica oleracea L. var alboglabra were enhanced when grown in 75% of peatgro mixed with 25% of coconut coir dust or 25% of rice husk. This combination contributes the high amount of nitrogen and calcium concentration in shoot tissues. Besides that, the plants grown in these substrates had high fresh and dry weight of shoot, number of leaves, total leaf area and plant height. Peatgro alone is not recommended to be used as growing medium because of its low water holding capacity, pH, shoot fresh and dry weight and total leaf area.